Recurrent outflow obstruction of a choked catheter for peritoneal dialysis caused by a fallopian tube fimbria in a five-month-old female - Ryoya Furugane (Elsevier, 2022)
Outflow obstruction of a catheter for peritoneal dialysis (PD) is one of the most common complications in patients who are undergoing PD for renal failure. Although the cause of catheter obstruction is variable, a choked catheter caused by a fallopian tube fimbria is quite rare and only five pediatric cases were reported. We report a case of a five-month-old female who suffered from recurrent catheter obstruction by a fallopian tube fimbria. Laparoscopic surgery was performed to recanalize the catheter, but the catheter obstruction recurred three days after the surgery. We abandoned the use of the catheter that had been inserted into the Douglas fossa and a new catheter was inserted into the left para-colonic groove. After the second surgery, catheter obstruction did not occur and PD has been continued without any complications.